Byin rlabs bla sgrub sdug bsṅal mun sel thugs rjeʼi ñi ʼod phyi naṅ gsaṅ gsum ñams su len paʼi zin bris bklags chog tu bkod pa yon tan ʼbyuṅ gnas : a text from the liturgy connected with the Gʼyu thog sñiṅ thig - Koṅ-sprul Blo-gros-mthaʼ-yas, 1813-1899 ([s.n.], 1969)
Ritual for obtaining blessings of the guru and spiritual welfare.